(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Direct evaporative cooling (DEC) is a passive cooling strategy adopted in predominantly hot regions to restore building thermal comfort with less energy consumption and minimum impact on the environment. The implementation and studies of DEC in tropical housing are limited. Although DEC can reduce air temperature, an increase in relative humidity can still be seen as a disadvantage. Many materials were introduced for the cooling pads, but none was explicitly proposed for use in the housing unit. The present study explores different cotton-based fabrics to be used in the proposed evaporative cooler of the public housing unit in Surabaya. It analyses its ability to reduce air temperature and identify the increase in air humidity that may occur. A small-scale model of the housing unit that incorporates an evaporative cooling system is set, and internal air temperature and humidity are recorded. Results of the analysis show that different fabric specifications can lead to various thermal performances. A cotton-based blanket is found to be suitable for the proposed strategy.